Hysteretic models that incorporate strength and stiffness deterioration. - Ibarra, Luis F. (Earthquake engineering & structural dynamics.)
This paper presents the description, calibration and application of relatively simple hysteretic models that include strength and stiffness deterioration properties, features that are critical for demand predictions as a structural system approaches collapse. Three of the basic hysteretic models used in seismic demand evaluation are modified to include deterioration properties : bilinear, peak-oriented, and pinching. The modified models include most of the sources of deterioration : i.e. various modes of cyclic deterioration and softening of the post-yielding stiffness, and also account for a residual strength after deterioration. The models incorporate an energy based deterioration parameter that controls four cyclic deterioration modes : basic strength, post-capping strength, unloading stiffness, and accelerated reloading stiffness deterioration. Calibration of the hysteretic models on steel, plywood, and reinforced concrete components demonstrates that the proposed models are capable of simulating the main characteristics that influence deterioration. An application of a peak oriented deterioration model in the seismic evaluation of single degree of freedom (SDOF) systems is illustrated. The advantages of using deteriorating hysteretic models for obtaining the response of highly inelastic systems are discussed.